Exploiting an investment opportunity based on ESG Score - Grileiro, Joana Rita Baleia (2019)
The attitude of society towards the environment, good human and management practices is becoming more important and is therefore having a strong impact on the financial world. In this sense, there has been a broad discussion among investors about the topic when building their stock portfolios. Is it worth it to invest only in accordance with our values and principles? The empirical analysis consider returns of trading strategies built on company corporate social responsibility (CSR) as measured by Environmental, Social and Governance indicators (ESG) retrieved from the Thomson Reuters Datastream for the S&P 500 Index from 2002 to 2016. The results of the study point out that investors can increase their performance following a simple investment strategy based on ESG Score but in reverse. Using ESG Score as a starting point, an investor should buy the stocks with the lowest ESG Score and selling the stocks with the higher values. This trading strategy leads to high abnormal returns of up to 7,92% per year and an annualized Sharpe ratio of 1,06. Investors should adopt this trading strategy and invest in projects that encourage initiatives that meet their values and convictions.